FROM SCRIPTORIUM TO DIGITAL ARCHIVE: The Transformation of Qur’anic Philology in The Technological Era - Nisa’, Lia Khoirotun; Mufid, Abdul; Syaiful, Muhammad (Program Studi Ilmu Al-Qur'an dan Tafsir, Universitas Islam Negeri Datokarama Palu, 2025)
Digital transformation has profoundly influenced the practice of Qur’anic philology, a discipline focused on the critical study of the history of transmission, authenticity, and reading variants of the sacred text. This study aims to analyze the impact of advancements in digital technology on working methods, source accessibility, and the repositioning of scholarly authority within Qur’anic philological studies. Using a literature review method and a historical comparative approach applied to twenty primary and secondary sources including digital case studies such as Corpus Coranicum and e-Mushaf this research examines how traditional methods once centered in scriptoriums have undergone transformation through digital archive platforms and modern analytical tools. The findings indicate that digitalization not only expands the global reach of Qur’anic manuscript preservation and distribution but also introduces epistemological challenges, such as textual decontextualization, digital literacy gaps, and shifts in authority from classical scholars and philologists to technology developers and digital curators. On the other hand, digitalization fosters unprecedented cross-disciplinary and transnational collaboration, while simultaneously demanding renewed reflection on methodological principles and scholarly ethics. As a conceptual contribution, this study proposes a framework for Digital Qur’anic Philology (DQP), emphasizing the integration of traditional textual precision with contemporary technological capabilities. The study concludes that digital archives function not merely as tools for preserving textual heritage, but also as catalysts for shaping new epistemic horizons in Qur’anic studies. Therefore, strengthening digital literacy and epistemological awareness becomes essential for safeguarding the authenticity and integrity of Qur’anic philology in the technological era.